Elevated pCO2 Affects Feeding Behavior and Acute Physiological Response of the Brown Crab Cancer pagurus - Wang, Youji; Hu, Menghong; Wu, Fangli; Storch, Daniela; Pörtner, Hans-Otto (Frontiers in Physiology, 2018)
Anthropogenic climate change exposes marine organisms to CO2 induced ocean acidification (OA). Marine animals may make physiological and behavioral adaptations to cope with OA. Elevated pCO2 may affect metabolism, feeding and energy partition of marine crabs, and thereby affect their predator-prey dynamics with mussels. Therefore, we examined the effects of simulated future elevated pCO2 on feeding behavior and energy metabolism of the brown crab Cancer pagurus. Following 54 days of pre-acclimation to control CO2 levels (360 μatm) at 11 °C, crabs were exposed to consecutively increased oceanic CO2 levels (two weeks for 1200 and 2300 μatm, respectively) and subsequently returned to control CO2 level (390 μatm) for two weeks in order to study their potential to acclimate elevated pCO2 and recovery performance. Standard metabolic rate (SMR), specific dynamic action (SDA) and feeding behaviour of the crabs were investigated during each experimental period. Compared to the initial control CO2 conditions, the SMRs of CO2 exposed crabs were not significantly increased, but increased significantly when the crabs were returned to normal CO2 levels. Conversely, SDA was significantly reduced under high CO2 and did not return to control levels during recovery. Under high CO2, crabs fed on smaller sized mussels than under control CO2; food consumption rates were reduced; foraging parameters such as searching time, time to break the prey, eating time and handling time were all significantly longer than under control CO2, and prey profitability was significantly lower than that under control conditions. Again, a two-week recovery period was not sufficient for feeding behavior to return to control values. PCA results revealed a positive relationship between feeding/SDA and pH, but negative relationships between the length of foraging periods and pH. In conclusion, elevated pCO2 caused crab metabolic rate to increase at the expense of SDA. Elevated pCO2 affected feeding performance negatively and prolonged foraging periods. These results are discussed in the context of how elevated pCO2 may impair the competitiveness of brown crabs in benthic communities.